(untitled) (Journal of Engineering, 2008)
Electrocoagulation is an electrochemical method of treating polluted water. Electrocoagulation and electroflotation are two techniques involving the electrolytic addition of coagulation metal ions directly from sacrificial electrodes by introducing an electrical current into the medium for the treatment of a wide range polluted water in an even wider range of reactor design, application of an electrical field prompts electrolysis of the water medium and generates particular quantities of hydrogen gas. The process works best with water’s pH in range 7.0-7.5 and will still often work less efficiently in the range 3.5 <pH<9.The effects of electrocoagulation process are in reduction water turbidity in relation to electrical current and operation period. The Electrocoagulation process gives removal efficiency of turbidity by about 85% for batch process and by about 62% for continuous flow and removal efficiency of total suspended solid by about 96% for batch process and 66% for continuous process. The optimum temperature was found to be at 35 C0 to give high efficiency in removal of turbidity, total suspended solid and sulphate ions.